Hubungan Asupan Zat Gizi dan Emotional Eating dengan Kejadian Obesitas - Khamidah, Adjeng Faricka; Iwaningsih, Sri; Ningtyas, Luthfiana Nurkusuma (Poltekkes Kemenkes Semarang, 2024)
Background: Obesity is an imbalance between energy incoming and expended by the body is characterized by the accumulation of fat in adipose tissue. Obesity as an adult is at risk of suffering from degenerative diseases. The prevalence of obesity among Civil Servants (PNS) in DKI Jakarta Province is 24.70% (Ministry of Health, 2018).Objectives: To determine the relationship between nutrient intake and emotional eating with the incidence of obesity in employees at the South Jakarta Community Health Center Area.Methods: This type of quantitative research with a cross-sectional design. The population in this study was 160 employees, with a sample size of 105 respondents. The sampling technique uses stratified sampling. Analysis used chi-square and Fisher's exact tests.Results: Show’s that there is a relationship between energy intake, protein, fat, carbohydrates, and emotional eating with the incidence of obesity, and there is no relationship between fiber and the incidence of obesityConclusion: It was concluded that the incidence of obesity was influenced by energy intake (p = 0.003, PR = 2.182), protein (p = 0.000, PR = 2.197), fat (p = 0.00, PR = 0.000), KH (p = 0.006, PR = 2.156), emotional eating (p = 0.002, PR = 1,810), although not fiber intake (p = 1.000).